Arsitektur Tradisional Rumah Adat di Kabupaten Malaka sebagai Respon Adaptif terhadap Bencana Alam (Hujan/Banjir) - Femilia Sinta Tefa; Serviana Evi Mali; Evalinda Florida Nahak; Maria Anisia Seran; Ince Metriana Fahik; Damian Puling; Yohanis Kristianus Tampani; Yuventus Tamela; Augusta De Jesus Magalhaes (Journal Innovation In Education, 2025)
This study aims to examine how the traditional architecture of vernacular houses in Malaka Regency, East Nusa Tenggara, adaptively responds to extreme environmental conditions, particularly heavy rainfall and seasonal flooding. Traditional houses, as products of local cultural heritage, demonstrate design strategies that reflect not only cultural values but also ecological functions. The method used is a qualitative approach involving field studies, direct observation, and interviews with traditional leaders and local communities. The findings indicate that architectural elements such as stilt-house structures, natural materials that dry easily, steeply sloped roofs, and rational drainage systems represent forms of adaptation to the threats of rain and flooding. These traditional houses serve not only as symbols of cultural identity but also as expressions of local wisdom in creating disaster-resilient dwellings. This study emphasizes the importance of preserving and developing traditional architecture as a sustainable solution to address climate change and the risks of natural disasters in rural areas.